A Review On the Possibility of Using the Video Data Bus Standard in Aviation for Smart Vehicles - Pamuk, Aslihan; Sakarya, Ufuk (Konya Teknik Univ, 2023)
One of the most important problems in real time systems is that the data collected from the sensors cannot be transferred from the sensors to the command and control system at a sufficient speed. This process is done via data bus. In this article, a review is made on the possibility of using the video data bus standard used in aviation in digital communication for smart vehicles in land transportation. While this review is being done, only a technical review is made. The main motivation in this article; it is to raise awareness by informing the people who develop smart vehicle systems in land transportation about the developments in the field of aviation. The capabilities of transportation vehicles in one transportation area can be a source of inspiration for vehicles in another transportation area when appropriate. There have been studies on the use of multiple sensors and their real-time transmission in the aviation field for a long time. Especially when the speed issue is brought forward, the necessity of fast communication arising from the speed requirements of aircraft has led to many studies in this field. In this article, after introducing the video data bus standard used in aviation in technical terms, comments on its possible use in automotive are presented. In the future, with the increase of sensors and cameras for smart vehicles, the demands of data transmission speed may increase even more. In autonomous vehicles, just as in aviation, it is very important to transmit information from sensors and cameras both quickly and reliably. It is envisaged that examining the features of the video bus in aviation, specific to the needs of the automotive industry, will be important in the design of the busses of the smart vehicles of the future.
Keywords: Intelligent Transportation Systems; Video Data Bus In Aviation; Multi-Sensors; SYSTEMS; Engineering